2016
DOI: 10.4314/agrosh.v16i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Yield differentials among participating and non-participating rice farmers in public/private partnership in Benue and Ogun states, Nigeria

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…However, cumbersomeness associated with opening credit account and delays in farmland assessment were not considered as serious constraints by TFM beneficiaries. This appears to agree with the findings of Akinwale, Ladele and Olajide, (2016) that reported better access to agricultural support services by participating farmers compared to non-participating farmers. Therefore, it implies that while TFM administrators strived to eliminate impediment in farmland assessment and opening and documentation formalities, it is apparent that the Banks need to work on fast tracking disbursement; guarantee certificate and processing of interest draw back.…”
Section: Respondents' Socioeconomic Characteristicssupporting
confidence: 91%
“…However, cumbersomeness associated with opening credit account and delays in farmland assessment were not considered as serious constraints by TFM beneficiaries. This appears to agree with the findings of Akinwale, Ladele and Olajide, (2016) that reported better access to agricultural support services by participating farmers compared to non-participating farmers. Therefore, it implies that while TFM administrators strived to eliminate impediment in farmland assessment and opening and documentation formalities, it is apparent that the Banks need to work on fast tracking disbursement; guarantee certificate and processing of interest draw back.…”
Section: Respondents' Socioeconomic Characteristicssupporting
confidence: 91%
“…Observations showed that sometimes farmers had difficulties of benefiting from available loan due to certain socioeconomic constraints such as level of education, accessibility to financial institution, farm size, membership of associations, contact with extension agents, and so on (Akinwale et al, 2016;Agbo et al, 2015). The unforeseen circumstances surrounding agriculture have made it an uphill task for farmers to obtained loan from financial institutions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the difficulty of smallholder farmers who produce more than 85% of domestic food supply to participate in agricultural credits/loans has remained a fundamental problem, despite the provision of financial aids by the government. Sub-Saharan African agriculture generally suffers this fate and this explains the socioeconomic characteristics of farmers and the nature and state of agricultural production across the African sub region (Adewunmi and Omotesho, 2002;Tchale, 2009;Omiti et al, 2009;Akinwale et al, 2016).…”
Section: Introductionmentioning
confidence: 99%